Analysis of Cause of Power Distribution Network Failures Using the Fault Tree Analysis Method at PT PLN Persero ULP Kuranji - Nurul Azmi; Julsam Julsam; Akbar Abadi (LPPM Universitas Andalas, 2026)
Electricity is a fundamental necessity in modern life, making the reliability of power distribution systems critical for consistent energy delivery to consumers. PT PLN (Persero) ULP Kuranji is responsible for power distribution in its service area, but frequent disturbances still compromise service quality. This study aims to identify and analyze the root causes of these distribution network failures using the Fault Tree Analysis (FTA) method, specially at ULP Kuranji using 2024 data. Data were gathered through literature review, field observations, and interviews with the Technical Team Leader of ULP Kuranji. The research methodology involved failure identification, fault tree construction, minimum cut set determination, and FTA-based analysis to formulate corrective recommendations. The results show that disturbances are mainly caused by external factors such (vegetation, weather conditions, animals, and third-party interference), an internal issues (component and equipment failures within the Medium Voltage Network (MVN). The analysis identified five basic events as primary root causes: natural disturbances, animal or third-party interference, component failures, material or equipment faults, and installation errors. Recommended mitigation measures include routine maintenance, protective risk inspection, adopting monitoring technologies, and infrastructure/equipment upgrades.